Aspects Regarding Some Theories Preceding the Emergence of the New Public Management - Florina POPA (Communications of International Proceedings, 2020)
The forms of manifestation of public administration, present until the end of the last century, were based on the traditional model, an expression of the principles of bureaucracy formulated by theoreticians of the time. The study follows the forms of approach of public administration and the theories that they were based on, prior to the emergence and development of the New Public Management (classical and neoclassical public administration, respectively, the theory of public choice, the new public administration, public management). Briefly, some elements of the theories formulated are presented, as well as their representatives, which generated the initiation of reforms and changes in the administration. The conclusions of the study point out, among other things, the fact that the management formula applied in the administration is not unique, but differs by countries, depending on the existing public administration and the priorities required for its proper functioning. The aim of the paper was to capture the main moments and forms of changes in the administration that evolved towards the paradigm shift and the emergence of the New Public Management. The research methodology was based on the identification and study of some materials from the foreign and autochthon specialized literature, corresponding to the chosen topic, the processing of the selected ideas and the author's own interpretation.
Keywords: Public Administration; Classical; Neoclassical; Theories.